2012
DOI: 10.1530/eje-11-0679
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal involvement in MEN1. Analysis of 715 cases from the Groupe d'étude des Tumeurs Endocrines database

Abstract: Adrenal pathology in MEN1 differs from that observed in sporadic incidentalomas. In the absence of relevant symptoms, endocrine biology can be restricted to patients with adrenal tumours and should focus on steroid secretion including the aldosterone-renin system. MEN1 is a high-risk condition for the occurrence of ACCs. It should be considered regardless of the size of the tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 42 publications
1
128
1
2
Order By: Relevance
“…Adrenal lesions have been described and vary: either bilateral or unilateral, including adrenal enlargement, adenomas, macronodular adrenal hyperplasia and adrenal cancer. The frequency of adrenal lesions range between 9 and 73% depending on the screening methods used (34). …”
Section: Multiple Tumors Syndromes Associated With Pbmahmentioning
confidence: 99%
“…Adrenal lesions have been described and vary: either bilateral or unilateral, including adrenal enlargement, adenomas, macronodular adrenal hyperplasia and adrenal cancer. The frequency of adrenal lesions range between 9 and 73% depending on the screening methods used (34). …”
Section: Multiple Tumors Syndromes Associated With Pbmahmentioning
confidence: 99%
“…The collection of clinical, biochemical, and genetic characteristics of unselected patients with rare disorders, such as MEN1, in multicentre-nationwide registries or databases, is a useful approach to increase knowledge of epidemiological aspects of the disease and the natural course and prognosis of single manifestations of the syndrome [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As for adrenal involvement in patients with MEN1, the data are contradictory with a prevalence ranging from 9 to 73% depending on the investigated series 1618 . A recent large study in 715 MEN1 patients showed adrenal lesions in 146 cases, and among them 72 had adrenal adenomas, comprising 10% of the whole cohort 5 . Four cases of PA were found in the whole group.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were attributed mainly to multiple endocrine neoplasia type 1 (MEN1), which is an autosomal dominantly inherited condition, characterized by the association of tumors of the pituitary and the parathyroid glands, the endocrine pancreas, the adrenal glands and neuroendocrine tumors 4 . Aldosterone-producing adenomas have been described in various combinations, mainly with hyperparathyroidism, prolactinomas and pancreatic endocrine tumors, but none of these have been associated with acromegaly 2, 3, 5 .…”
Section: Introductionmentioning
confidence: 99%